2016
DOI: 10.1007/s12640-016-9679-4
|View full text |Cite
|
Sign up to set email alerts
|

Kukoamine A Prevents Radiation-Induced Neuroinflammation and Preserves Hippocampal Neurogenesis in Rats by Inhibiting Activation of NF-κB and AP-1

Abstract: Impaired hippocampal neurogenesis and neuroinflammation are involved in the pathogenesis of radiation-induced brain injury. Kukoamine A (KuA) was demonstrated to have neuroprotective effects through inhibiting oxidative stress and apoptosis after whole-brain irradiation (WBI) in rats. The aim of this study was to investigate whether administration of KuA would prevent radiation-induced neuroinflammation and the detrimental effect on hippocampal neurogenesis. For this study, male Wistar rats received either sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
1
30
1
Order By: Relevance
“…TNF-α is a main pro-inflammatory cytokine, and is mainly produced by activated microglia during the neuroinflammation. Growing evidence showed that the overproduction of TNF-α by microglia contributes to pathophysiological changes observed in various neurologic diseases and brain injury [3, 29]. In addition to inflammation caused by ischemia/hypoxia, we also found CoCl 2 treatment induced cell apoptosis (Fig 2).…”
Section: Discussionsupporting
confidence: 52%
“…TNF-α is a main pro-inflammatory cytokine, and is mainly produced by activated microglia during the neuroinflammation. Growing evidence showed that the overproduction of TNF-α by microglia contributes to pathophysiological changes observed in various neurologic diseases and brain injury [3, 29]. In addition to inflammation caused by ischemia/hypoxia, we also found CoCl 2 treatment induced cell apoptosis (Fig 2).…”
Section: Discussionsupporting
confidence: 52%
“…The IL-1β and TNF-α levels were measured using commercial ELISA kits as per the manufacturer’s instructions. 21 …”
Section: Methodsmentioning
confidence: 99%
“…The results were recorded using Quantity One imaging software (Bio-Rad, Hercules, CA, USA), and relative intensities were calculated using Gel-Pro Analyzer software (Media Cybernetics, Bethesda, MD, USA). For some experiments, subcellular fractionation was performed using a Nuclear and Cytoplasmic Protein Extraction Kit (p0027, Beyotime Biotechnology, Shanghai, China) [ 36 , 37 ] and Tissue Mitochondria Isolation Kit (C3606, Beyotime Biotechnology) [ 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%